Implementing Secure Grid Services using Globus Toolkit - Ahuja, Rajwant Kaur (My University, 2007)
In Collaborative environment, security is very important. Numbers of threats exists, when communicating over network of computers, through which security can be broken and utilization of resources is done by intruder. Distributed Systems are those in which multiple different components of an application communicate and coordinate their action by passing messages. Numbers of resources, huge computing power and data are available in distributed systems environment. Hackers are looking for such useful systems only. Different techniques are implemented to secure distributed systems. A Network cannot be 100 percent secured, achieving security in distributed system is bit difficult but somewhat achieved with the use of various security techniques. Grid is an example of distributed system. “Grid enables the sharing, selection, and aggregation of geographically distributed resources dynamically at run time depending on their availability, capability, performance, cost, user quality-of –self-service requirement.” The heterogeneous nature of resources and their differing security policies are complicated and complex in the security schemes of a Grid Computing environment. The aim of this thesis is to provide awareness about existing security techniques in distributed systems, and how they are not sufficient if there is need to secure Grid environment. This thesis focuses on the basic Grid security problem, its requirements, Grid Security Infrastructure (GSI) and GT3 model for Open Grid Service Architecture (OGSA).
Keywords: Globus Toolkit; Grid Services